Pelancu Ecotourism Recovery Strategy in Ulak Pandan Village After the COVID-19 Pandemic - Sasua Hustati Syachroni; Asvic Helida; Imam Mahni (Universitas Muhammadiyah Palembang, 2024)
The pandemic conditions caused by Covid-19 have caused a quite drastic decline in the tourism sector in Indonesia, even though the tourism sector contributes as a source of income for the country. This research aims to increase the potential of Pelancu ecotourism by implementing a strategy to develop Pelancu ecotourism after the Covid-19 pandemic. This research was carried out in Ulak Pandan Village, West Merapi District, Lahat Regency, South Sumatra Province from September to November 2022. The research method used qualitative methods. Descriptive analysis, in collecting samples, descriptive data is produced in the form of words or verbally from several sources, namely the village government including the Village Head and BPD (Village Consultative Body), tourism managers, and the surrounding community as well as Pelancu Tourism tourists. The research results show that the condition of Pelancu Tourism after the Covid-19 pandemic is well maintained, cool and beautiful. The arrangement of the Pelancu Tourism area is maintained, especially the cleanliness of the surrounding environment, which is the responsibility of the Pelancu Tourism object management. Some of the shortcomings found after the Covid pandemic were that the management did not pay enough attention to the infrastructure at Pelancu Tourism. The strategy for restoring Pelancu ecotourism in Ulak Pandan Village that the management will carry out is by adding several facilities such as the addition of children's park play equipment and infrastructure such as family food huts, photo-taking rides to attract the interest of tourists who come to Pelancu Tourism like before the Covid-19 pandemic. happen. Then by promoting it on social media, including Instagram, Facebook, etc. By updating posts on the Pelancu Tourism website and social media.